KONSEP PENDIDIKAN TÃNGKÃ (MORAL) MENURUT K.H. ABD HAMID BIN ISTBAT (1868-1933) BANYUANYAR PAMEKASAN (STUDI ANALISIS ATAS KITAB TARJÃMÃN) - Syarif, Zainuddin (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2018)
K.H. Abdul Hamid in the Tarjuman Kitab states that Moral Education (Tengka) is an education concept of the effort to grow the awareness of the students (santri) to make them a better person in the world and the life after. This concept is putting forward the ethics (Akhlaq) than the intellectual development. There are some points in emphasizing Moral Education (Tengka) of K.H. Abdul Hamid in the Tarjuman Kitab. First, this education concept using philosophical-anthropological paradigm. Here it states that human being is Abdul Allah (hamba) and Khalifah Allah (the substitutes in the world). In this book, there are many explanation about Ethics related to the relationship to Allah and relationship with human beings. Islam itself has set how they should keep their attitude well which will be useful for himself and his environment including for others. Secondly, this education is stressed more on internalizing the awareness of Tauhid to every student (santri) in the pesantren or school to make them know the pure characteristic of human being. The third, Moral Education (tengka) of K.H. Abdul hamid in the Tarjuman Kitab is obviously implemented in Pondok Pesantren Banyuanyar Pamekasan Madura. Fourth, Moral Education (tengka) K.H Abdul Hamid in the Tarjuman Kitab is still suitable with the Character based Education which is developed in Indonesia.